Ghosts that are not ghosts: The domesticated un-ghost in Victorian fiction. Issue 2 (21st October 2011) - Branca, R. Renee
Although the ghost has been a standard literary device for centuries, how that device is used, what the ghost represents within the framework of the narrative, the purposes for manifestation, authorial intention and even reader expectation of haunting is constantly challenged. This article focuses on the shift of narrative haunting from its eighteenth-century Gothic roots to its centrality in Victorian fiction by offering a close reading of particular entities appearing in canonical Victorian texts by Brontë, Collins, Dickens, Braddon, James and Le Fanu, establishing their relationship to the template, and then analyses the metamorphosis of form based on historical, social, scientific and epistemological context.